(untitled) (The Review of Diabetic Studies, 2026)
Ensuring high-quality care in the modern healthcare environment demands innovation, flexibility, and effective leadership. In particular, nurse managers play a pivotal role in staff management, care delivery, and organizational change, which requires them to be competent in entrepreneurial leadership (EL), hold positive attitudes toward artificial intelligence (AI), and foster innovative work behavior (IWB). Considering how these factors influence IWB among nurse managers, this systematic review examined 16 studies published between 2020 and 2025. A comprehensive literature search was conducted in PubMed, Scopus, Google Scholar, and CINAHL, in addition to manual searches of the Journal of Nursing Management, using keywords related to EL, AI, IWB, nurse managers, and healthcare innovation. The included studies were original research articles with quantitative, qualitative, or mixed-method designs that specifically addressed nurse managers or frontline nurses in healthcare settings. Reviews, theses, and nonempirical studies were excluded. The findings indicate that EL fostered IWB by significantly enhancing nurse managers’ decision-making, opportunity recognition, knowledge sharing, and creativity. In addition, positive attitudes toward AI act as predictive and mediating variables supporting technological adoption, workflow optimization, and problem-solving. Organizational support systems, including training, resources, and autonomy, are critical enablers that translate EL and attitudes toward AI into tangible innovation. The integration of EL, technological readiness, and contextual support collectively drives sustainable IWB. Future research should explore the longitudinal impacts of EL and AI-focused interventions, assess scalability across diverse healthcare contexts, and examine how systemic support can be optimized to further enhance nurse managers’ innovative capacity and organizational performance.